ANALISIS TANAMAN OBAT YANG MENJADI PRIORITAS UNTUK DIKEMBANGKAN DI JAWA TENGAH - Nurul Husniyati Listyana (Universitas Sebelas Maret, 2016)
The aim of this study is to analyze the index Location Quotient of ginger, kencur, turmeric and galangal; to analyze the value of the growth component of ginger, kencur, turmeric and galangal; to analyze the types of medicinal plants is a priority for development in Central Java. This research uses descriptive method with secondary data sources coming from the Badan Pusat Statistik. In this study analyzed the competitiveness of the four regions, namely medicinal plant ginger, kencur, turmeric and galangal. The results showed Ginger has LQ <1 while kencur, turmeric and galangal has LQ> 1. Ginger has a value component of positive growth while kencur, turmeric and galangal has a negative value. Ginger has a value of share growth component negative territory while kencur, turmeric and galangal has a positive value. Kencur, turmeric and galangal is a commodity that is becoming a priority for development in Central Java Province.